(untitled) (Research, Society and Development, 2021)
Objective: To investigate the itinerary of users who had access to the antifibrotic drugs nintedanib and pirfenidone via judicial or administrative procedures; as well as their respective socioeconomic and epidemiological profiles served by the Judicial and Administrative Demands Pharmacy. Method: This is a cross-sectional, retrospective, analytical-descriptive, qualitative-quantitative study. The socioeconomic and demographic data of the users are presented. Results: The findings inform us that there is a prevalence of demand through the administrative process in relation to the demand through the courts. Users find it difficult to register, renew and access the medicine; therefore, they present difficulties for adherence and continuity of treatment. Conclusion: It is inferred that there are difficulties in accessing treatment for IPF in Pará, and treatment adherence and continuity are hampered by the inconstancy in the acquisition of antifibrotics. There is damage to the quality of life of users. There were high expenses with the acquisition of antifibrotic drugs.